PENERAPAN PROGRAM ADIWIYATA DALAM PENGEMBANGAN KARAKTER PEDULI LINGKUNGAN (STUDI KASUS SMA NEGERI 5 PADANG) - Mutia Ainil Hasan; sri Mariya (JURNAL BUANA, 2021)
This study aims 1) to determine the implementation of the Adiwiyata Program, 2) to determine the challenges faced by SMAN 5 Padang in the Adiwiyata Program of SMAN 5 Padang, 3) and to determine the efforts made by SMAN 5 Padang in involving students to participate in the Adiwiyata Program. This research method is qualitative and the location of this research is in SMAN 5 Padang. The data used in this study are primary data and secondary data. The technique of determining informants using purposive sampling and data collection techniques in this study using observation, interview, and documentation techniques. Data analysis techniques by means of data reduction, data presentation, and drawing conclusions. The results of this study are: 1) SMAN 5 Padang in the application of the Adiwiyata Program has fulfilled the Adiwiyata components, namely the establishment of school policies, implementation of environment-based curricula, environmental-based Adiwiyata Program activities and complete facilities and infrastructure to support the Adiwiyata Program. 2) The challenges faced by SMAN 5 Padang in implementing the Adiwiyata program are habits shown by the value of caring for the environment through student habituation. 3) Efforts made in the implementation of the Adiwiyata Program are teacher exemplary, punishment for students whose behavior can damage the school environment and reward for students who have a caring character for the environment.